Redescription of Chironomus javanus and Chironomus kiiensis (Diptera: Chironomidae) Larvae and Adults Collected from a Rice Field in Pulau Pinang, Malaysia - Salman A Al-Shami; Che Salmah Md Raw; Abu Hassan Ahmad; Siti Azizah Mohd Nor (Tropical Life Sciences Research, 2012)
Chironomus javanus (Kieffer) and Chironomus kiiensis Tokunaga were redescribed from materials collected from a rice field in Pulau Pinang, Malaysia. The larvae can only be distinguished after careful preparation and examination using a compound microscope, but the pupae were not useful to differentiate C. javanus from C. kiiensis. The adult specimens showed clear body and wing characteristics for rapid and accurate identification. Chironomus javanus (Kieffer) dan Chironomus kiiensis Tokunaga dihuraikan semula menggunakan specimen yang dikumpul daripada sebidang sawah padi di Pulau Pinang, Malaysia. Larva hanya boleh dibezakan selepas persediaan dan pemeriksaan specimen yang teliti menggunakan mikroskop majmuk, tetapi pupanya tidak sesuai digunakan untuk membezakan antara C. javanus dan C. kiiensis. Specimen dewasa menunjukkan ciri-ciri badan dan sayap yang jelas untuk pengecaman yang cepat dan tepat.